Dosage and Ferritin Reduction in Paediatric Thalassemia Major: A Cross-Sectional Study - Athiah, Medina; Zikra, Muhamad; Safyudin; Lestari, Hertanti Indah; Fatmawati (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Thalassemia is a genetic disorder that requires regular blood transfusions, often resulting in iron overload. Iron chelation therapy with deferiprone is commonly used to manage the iron overload, yet the relationship between deferiprone dosage and ferritin level reduction remains unclear. This study aimed to find out how the dose of deferiprone affects the reduction of serum ferritin levels in children with thalassemia major. A cross-sectional analytical study was conducted involving 69 paediatric patients with thalassemia major receiving deferiprone therapy at Dr. Mohammad Hoesin Central General Hospital, Palembang. Data on patient demographics, transfusion frequency, deferiprone dose, and serial ferritin levels (3–6 months apart) were collected. The optimal dose cut-off was determined using ROC analysis, and statistical association was tested using the Chi-Square test. Most patients (56.5%) received deferiprone doses ≤77.95 mg/kgBW. Only 36.2% achieved a ferritin reduction of ≥20%, while 50.7% experienced increased ferritin levels. No statistically significant association was found between deferiprone dose and ferritin reduction (p = 0.051), although a trend toward lower success in the high-dose group was observed (PR 0.355, 95% CI: 0.124–1.019). The average dose of deferiprone administered in this study was below the minimum dose recommended by the FDA, which may explain the lack of significant association with serum ferritin reduction. Further research with controlled dosing and exclusion of confounding variables is recommended to evaluate deferiprone effectiveness more accurately